Smoking effects on renal and central hemodynamics in men and women with essential arterial hypertension - V. I. Podzolkov; A. E. Bragina; Yu. N. Rodionova (Кардиоваскулярная терапия и профилактика)
Aim. To compare renal and central hemodynamic parameters in smoking and non-smoking men and women with essential arterial hypertension (EAH).Material and methods. In 135 patients (50 men and 85 women) with Stage 2-3 EAH, renal angioscintigraphy and echocardiography were performed.Results. In smokers, significant gender differences in renal hemodynamics were observed. For left kidney, blood flow levels were 484,3±81,2 and 266,7±68,5 ml/min in men and women, respectively (р=0,000); for right kidney — 478,3±85,9 and 263,3±70,3 ml/min, respectively (р=0,000). Gender differences in renal blood flow were also significant in non-smoking men and women, with left kidney blood flow levels of 389,0±90,7 and 232,2±69,9 ml/ min (р=0,000), and right kidney levels — 396,0±91,5 and 239,5±75,5 ml/min, respectively (р=0,000). Total glomerular filtration rate (TGFR) in smoking women was significantly lower (117,0±11,5 ml/min) than in smoking men (132,4±17,2 ml/min; р=0,01). Among non-smoking men and women, this parameter was 107,5±24,6 and 147,3±38,5 ml/min, respectively (р=0,000). Compared to their non-smoking peers, smoking men demonstrated higher left ventricular myocardial mass index (LVMMI): 147,8±20,8 vs. 129,1±15,7 g/m2 (р=0,002). For smoking and non-smoking women, the respective figures were 118,9±13,1 and 109,1±11,2 g/m2 (р=0,015). Significant gender differences were also observed for total peripheral vascular resistance (TPVR) in smoking (р=0,000) and non-smoking (р=0,000) EAH patients.Conclusion. Women with EAH, regardless of their smoking status, demonstrated significantly lower renal blood flow and TGFR, as well as significantly higher TPVR, than men from respective smoking status groups. Smoking men had significantly higher renal blood flow levels than non-smoking men. Regardless of gender, LVMMI was higher among smokers.